Analisis Pertumbuhan Ekonomi, Produksi Tanaman Pangan dan Ketahanan Pangan di Propinsi Jambi - Rahayu, Silvia; Dorris Yadewani (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This research aims to analyze economic growth, food crop production and food security in Jambi Province. The data used in this research is secondary data obtained from the Jambi Province BPS website. This research was conducted for 1 month. Data analysis method uses qualitative and quantitative descriptive methods. The analysis tools used are multiple linear regression, hypothesis testing and coefficient of determination. The research results showed that there was partially no effect of economic growth on food security in Jambi Province and no effect of food crop production on poverty in Jambi Province. Simultaneously, there is a significant influence between economic growth and food crop production on food security in Jamb Province. The simultaneous influence between Economic Growth and food crop production on food security in Jambi Province is 79.2%, the remaining 20.8% is influenced by other variables not examined in the research.